Theoretical and Methodological Basis and the Concept of a sustainable Development of the Integrated structures of Business Теоретико-методологический базис и концепция устойчивого развития интегрированных структур бизнеса - Yaldin Igor V. (Problemi Ekonomiki, 2010)
In article results of the research directed on working out of theoretical and methodological basis of stable development of integrated structures of business (ISB) at different stages of their life cycle are presented. The research hypothesis is generated. The idea is put in its basis about possibility of creation of a contour of management by stable development of the integrated association of subjects of managing. Principles of maintenance of firmness of development ISB and laws of management are defined by proof development ISB. The list of conceptual positions which it is offered to base on practical realization of a hypothesis is developed. В статье представлены результаты исследования, направленного на разработку теоретико-методологического базиса устойчивого развития интегрированных структур бизнеса (ИСБ) на разных этапах их жизненного цикла. Сформирована гипотеза исследования, в основу которой положена идея о возможности создания контура управления устойчивым развитием интегрированного объединения субъектов хозяйствования, при рассмотрении интеграции как механизма формирования пула комплиментарных компетенций. Определены принципы поддержания устойчивости развития ИСБ и закономерности управления устойчивым развитием ИСБ. Разработан перечень концептуальных положений, которые предлагается положить в основу практической реализации гипотезы.